Norbert Elias and Modern Sociology Knowledge, Interdependence, Power, Process - Dunning, Eric (Bloomsbury Academic, 2012)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. This book explores the interplay between the making of Elias as a sociologist and the development of his core ideas relating to figurations, interdependence, and civilising processes. Focusing on the relevance of Elias's work for current debates within sociology, the authors centrally consider his contributions to the sociology of knowledge and methodology. Dunning and Hughes locate the work of Elias within a discussion of the crisis of sociology as a subject, and compare his figurational approach with the approaches of three major figures in modern sociology: Anthony Giddens, Michel Foucault and Pierre Bourdieu. This highly readable and engaging book will be essential reading for students and scholars of sociological theory and methods.